Mainstreaming AICCRA CIS/CSA course modules in African Universities’ curricula - Nakayiwa, Florence Mayega; Egeru, Anthony; Majaliwa, Jackson Gilbert Mwanjalolo (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The deliverable reports the achievements of use of AICCRA CIS/CSA course modules in various universities in Africa. It highlights the mainstreaming of the course modules in BSc program in Tanzania (through revision of curricula) and in a new MSc program (Green Economy) Uganda (through the use in the creation of a new program). It also highlights the formal requests of the course modules by several universities from 14 African countries including 11 non-AICCRA countries.